2018
DOI: 10.1159/000495277
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Pretreatment Serum Apolipoprotein A1 and Prognosis of Solid Tumors in Chinese Population: A Systematic Review and Meta-Analysis

Abstract: Background/Aims: Serum apolipoprotein A1 (apoA1) has been reported to be abnormally expressed in several malignancies. However, the prognostic role of apoA1 in solid tumors is still controversial. We conducted this meta-analysis to obtain a more accurate evaluation of prognostic significance of apoA1 in Chinese patients with solid tumors. Methods: A comprehensive literature search of electronic databases was carried out up to August 2018. We included studies investigating the association between pretreatment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
(77 reference statements)
2
11
0
Order By: Relevance
“…In our study, HDL and apoA1 suppressed K562 viability and cellular cholesterol concentrations relative to LDL in a time-and LXR-dependent manner. In line with increased LXR-induced ABCA1 mRNA expression observed in our study, we additionally found that apoA1 suppressed K562 cell viability to a greater extent than HDL in LXR-treated cells at 48 and 72 h. ApoA1 has been shown to exhibit anticancer properties in in vitro studies, animal models, and clinical trials, and may additionally play an indirect role in protection from cancer through modulation of the tumor microenvironment and tumor-associated macrophage phenotypes (Wu et al, 2018;Zamanian-Daryoush et al, 2013;Zamanian-Daryoush and DiDonato, 2015). Despite differences in HDL and apoA1-mediated effects on K562 cell viability in our study, no significant differences in cholesterol content and mRNA expression of antiapoptotic BCL-XL and differentiation genes were observed between HDL and apoA1, suggesting that additional mechanisms may be involved in apoA1-mediated anticancer effects in K562 cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, HDL and apoA1 suppressed K562 viability and cellular cholesterol concentrations relative to LDL in a time-and LXR-dependent manner. In line with increased LXR-induced ABCA1 mRNA expression observed in our study, we additionally found that apoA1 suppressed K562 cell viability to a greater extent than HDL in LXR-treated cells at 48 and 72 h. ApoA1 has been shown to exhibit anticancer properties in in vitro studies, animal models, and clinical trials, and may additionally play an indirect role in protection from cancer through modulation of the tumor microenvironment and tumor-associated macrophage phenotypes (Wu et al, 2018;Zamanian-Daryoush et al, 2013;Zamanian-Daryoush and DiDonato, 2015). Despite differences in HDL and apoA1-mediated effects on K562 cell viability in our study, no significant differences in cholesterol content and mRNA expression of antiapoptotic BCL-XL and differentiation genes were observed between HDL and apoA1, suggesting that additional mechanisms may be involved in apoA1-mediated anticancer effects in K562 cells.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, hypercholesterolemia has been shown to adversely impact cancer risk and metastasis (Bielecka‐Dabrowa et al, 2011; Long et al, 2018), whereas LXR activation and cellular cholesterol efflux mediated by ABCA1‐ and ABCG1 has been shown to confer protection against cancer burden and progression (Bovenga et al, 2015; El Roz et al, 2012; Smith and Land, 2012). Interestingly, while some studies demonstrate that HDL and apoA1 exert protective effects in various cancer types (Su et al, 2012; Wu et al, 2018; Zamanian‐Daryoush et al, 2013), population‐based studies evaluating the association between HDL‐cholesterol levels and cancer parameters have yielded conflicting results (Pirro et al, 2018). Variability in the relationship between cancer and HDL‐related markers may be attributable to differences in HDL composition, which can greatly impact functionality (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Serum apoA-I is associated with the diagnosis of many types of cancer and the appearance of metastases. A meta-analysis revealed that apoA-I levels also predicted the prognosis of patients with various cancers treated with surgery, chemotherapy, radiotherapy, or immunotherapy [26]. mRNA and protein levels of apoA-I were reduced in HCC [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…An overall association of HDL/ApoA-I levels with the prognosis of cancer patients treated with surgery, chemotherapy, radiotherapy, or immunotherapy has been concluded in a recent meta-analysis [142]. Indeed, an association with prognosis has been reported in patients with nasopharyngeal carcinoma, non-small cell lung carcinoma, invasive breast ductal adenocarcinoma, esophageal squamous cell carcinoma, colorectal adenocarcinoma, HCC, renal cell carcinoma, and transitional cell carcinoma of the bladder [80,81,82,85,86,88,89,95,101,102,108,109,135,143].…”
Section: A Potential Protective Role Of Apoa-i Against Cancer: Evimentioning
confidence: 99%